A STUDY ON EFFICACY OF CORNEAL COLLAGEN CROSS LINKING IN PROGRESSIVE KERATOCONUS - Bodla, Ali Afzal; Bodla, Muhammad Afzal; Moazzam, Ayema; Kazmi, Minahil; Aman, Muhammad Muneeb (Journal of Ayub Medical College Abbottabad, 2021)
Background: Keratoconus is a progressive, noninflammatory, bilateral ectatic corneal disease, characterized by paraxial stromal thinning and weakening that leads to corneal surface distortion. The objective of this research was to determine the effectiveness and safety of collagen crosslinking in progressive keratoconus, with keratometry (Kmax) value of 50 diopters or above. It was a retrospective study, conducted at Bodla Eye Care (BEC) and Multan Medical and Dental College, Multan (MMDC) from May 2018 to November 2019. Methods: In this research 52 eyes were studied. The best-corrected visual acuity, uncorrected visual acuity, maximum keratometry, mean keratometry value, and thinnest corneal thickness before surgery and 12 months after Cross-linking were observed. A Galeili G6 by Zeimer ophthalmic system was used to measure the clinical parameters. Dresden protocol was followed in this study. A written ethical approval was obtained and research was conducted under the light of declaration of Helsinki. Results: The average logarithm of the minimum angle of resolution (logMAR) of the uncorrected visual acuity decreased from 0.66±0.41 D to 0.49±0.40 D (p=0.012), while the mean thinnest point thickness of the cornea decreased from 435.31 37.91 Î¼m to 419.41±70.12 Î¼m (p=0.004) after 12 months. The decreases in the mean logMAR of the BCVA, Kmax and Kmean values were not analytically important (p>0.05) at the 12-month follow-up 94.2% positive results were obtained. Conclusion: Collagen cross-linking treatment was safe and maintained both the visual acuity and tomographic parameters at the one-year follow-up in eyes.